A kinematic analysis of different jumping methods for spiking in volleyball - Chi, C. Y.; San, C. M. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This study was designed to analyze kinematic characteristics of different types of volleyball spikes at take-off. It compared the hop jump and step-close jump with different stride distances (25cm-35cm and 45cm-55cm). Twelve male college volleyball players volunteered for this study. The displacement of squatting, striding, and horizontal hop jumps were shorter than those data of step-close jump. However, when compared with vertical displacement, the performance of hop jump was better than step-cross jump. The angles of lower limbs during the hop jump landing, body mass center in the lowest position, and take-off were significantly narrower than those displayed during step-cross jump. Therefore, the step-close jump demonstrated significantly better kinematics compared to the hop jump.